Sinergi Penegakan Hukum antara Bidang Pidsus, Datun, dan Intelijen dalam Optimalisasi Kinerja Kejaksaan Negeri Palangka Raya - Destia Purwaningsih; Maulida Maulida; Nabela Nabela; Anita Sugiarti; Risatun Nada; Syahrul Mubarok; Novita Mayasari Angelia (Lembaga Pengembangan Kinerja Dosen, 2025)
This community engagement program aims to analyze and strengthen institutional synergy among the Special Crimes Division, the Civil and Administrative Affairs Division, and the Intelligence Division of the Palangka Raya District Prosecutor’s Office through a community-organizing framework and participatory collaboration. The initiative stems from a strategic need to optimize coordination, enhance the effectiveness of law enforcement, and foster the development of an integrated work pattern that is responsive to the complexities of contemporary legal issues. Using the participatory action research (PAR) method, the program was implemented through participatory assessments, thematic discussions, field observations, case simulations, and the strengthening of legal administration, all of which collectively contributed to substantial improvements in analytical capacity, professionalism, and cross-divisional communication patterns. The findings indicate that synergy across divisions not only enhances the technical efficiency of case handling but also generates institutional social change through the establishment of new work routines, the emergence of local leaders, and the strengthening of internal social capital. Theoretically, these outcomes reinforce perspectives from collaborative governance, organizational learning, and institutional change, which emphasize that institutional transformation can only be achieved through functional integration, knowledge exchange, and the cultivation of a collaborative institutional culture. This program recommends the institutionalization of coordination procedures, the utilization of information technology as a tool for data integration, and the implementation of continuous synergistic training to sustain the changes achieved. Consequently, this engagement contributes both empirically and conceptually to the development of an adaptive, integrated law enforcement model aimed at improving the quality of public service delivery.